Concerning CT features used to select patients for treatment of peritoneal metastases, a pictoral essay. (4th July 2017) - Sugarbaker, Paul H.; Sardi, Armando; Brown, Gina; Dromain, Clarisse; Rousset, Pascal; Jelinek, James S.
Abstract: Background: During the Fifth International Workshop on Peritoneal Surface Malignancy in Milan in 2008, a consensus was reached that contrast-enhanced CT (ceCT) was the principal imaging modality for patients being evaluated for treatment of peritoneal metastases. This fact being accepted, the radiologic criteria for that may exclude patients from a high value cytoreductive surgery (CRS) plus hyperthermic perioperative chemotherapy (HIPEC) have not been reliably determined. Methods: From a consensus of surgeons and radiologists, radiologic images were selected and their determinant radiologic characteristics described. The anatomic pathology causing the abnormal images were identified and characterised. The cytoreductive surgical procedures that may, in selected patients, result in a complete resection of the pathology identified were presented. Results: Radiographs of 15 CT images that cause concern when a patient is being evaluated for CRS were listed. The anatomic pathology these images define and possible surgical resections they require were reviewed. The surgical implications of the absence or presence of a single, or of multiple concerning CT features was extracted from the surgical and radiologic literature. Conclusions: There is a definite need to identify new pre-operative imaging parameters to define optimal indication of CRS with HIPEC. The presence of a single concerning radiologic feature is associated with the possibility of an adverse outcome or technically more complex resections associated with increased morbidity and mortality. If two or more of the concerning radiologic features are described from the CT, suboptimal cytoreduction will usually occur.